Review Methods for Estimating Loss of Life from Floods due to Dam Failure - Norkhairi, Fatin Faiqa; Thiruchelvam, Sivadass; Hasini, Hasril (International Journal of Engineering and Technology, 2018)
Dam is known as well build structure that stored high volume of water for various purposes such as irrigation, water supply and electricity generation. With the multiple usage of dam towards the nation and civilization, the dam should be properly examined so that it will not cause extreme effect in sociology, economics and environmental. However, dam may experience a failure due to many reasons. The aftermath of dam failure especially in term of loss of life could leave detrimental effects on human, properties as well as environment. Therefore, this paper provides a systematic review on the existing methods to estimate the loss of life due to the dam failure. Throughout the years, many improvements have been made to give better estimation for loss of life. Such prediction is very important for disaster planning by authorities.